Grain markets in Europe, 1500-1900 integration and deregulation - Persson, Karl Gunnar 1943-2016 (Cambridge studies in modern economic history, 1999)
In this 1999 book, Karl Gunnar Persson surveys a broad sweep of economic history, examining one of the most crucial markets - grain. His analysis allows him to draw more general lessons, for example that liberalization of markets was linked to political authoritarianism. Grain Markets in Europe traces the markets' early regulation, their poor performance and the frequent market failures. Price volatility caused by harvest shocks was of major concern for central and local government because of the unrest it caused. Regulation became obsolete when markets became more integrated and performed better through trade triggered by falling transport costs. Persson, a specialist in economic history, uses insights from development economics, explores contemporary economic thought on the advantages of free trade, and measures the extent of market integration using the latest econometric methods. Grain Markets in Europe will be of value to scholars and students in economic history, social history and agricultural and institutional economics